2013
DOI: 10.1038/sc.2013.14
|View full text |Cite
|
Sign up to set email alerts
|

Survival following spinal cord infarction

Abstract: Patients with spinal cord infarction appear to have a fair survival after discharge from in-patient rehabilitation, not withstanding the occurrence of risk factors of vascular disease in many patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Among those studies that investigated the causes of death, the reported leading causes of death were diverse (n = 22) [9,10,19,37,40,42,51,65,74,78,84,86,87,88,89,90,92,94,97,106,107,108,109]. The most commonly reported leading cause of death was pneumonia (n = 5) [19,51,78,94,109], followed by heart disease (n = 3) [10,74,84].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those studies that investigated the causes of death, the reported leading causes of death were diverse (n = 22) [9,10,19,37,40,42,51,65,74,78,84,86,87,88,89,90,92,94,97,106,107,108,109]. The most commonly reported leading cause of death was pneumonia (n = 5) [19,51,78,94,109], followed by heart disease (n = 3) [10,74,84].…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly reported leading cause of death was pneumonia (n = 5) [19,51,78,94,109], followed by heart disease (n = 3) [10,74,84]. Only one study reported the crude number of deaths for causes of mortality by gender, and found that the leading cause of death among males was heart disease, compared to an equal number of deaths due to digestive disorders as well as heart disease for females [84].…”
Section: Resultsmentioning
confidence: 99%
“…SCI in the setting of cardiac arrest and acute aortic rupture or dissection, and those with high cervical lesions are at greatest risk for fatality [5]. Patients with SCI have a persistently elevated mortality rate after hospital discharge [5,6,11,18,20,21]. In the largest study of 115 patients with SCI, 5-and 10-year survival rates were 55% and 42%, respectively [5].…”
Section: Clinical Presentation Etiology and Prognosismentioning
confidence: 98%
“…The acute fatality rate varies depending on the case mix in the retrospective analysis of patients [16][17][18][19][20]. SCI in the setting of cardiac arrest and acute aortic rupture or dissection, and those with high cervical lesions are at greatest risk for fatality [5].…”
Section: Clinical Presentation Etiology and Prognosismentioning
confidence: 99%
“…Aortic disease is the most common cause, most probably due to vulnerability of the thoraco-lumbar spinal cord to hypoperfusion [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Other aetiologies include atherosclerosis, adjacent spinal degenerative disease, fibrocartilaginous embolism (FCE), vertebral dissection, systemic hypotension, cardiac embolism, coagulopathies, vasculitides, surfing-related myelopathy and decompression sickness [1][2][3][4][5][6][7][8][9][10][11][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%